Cover Image. Issue 2 (4th February 2018) - Li, Zhuolun; Wei, Zhiqiao; Dong, Shipei; Chen, Qiujie
Abstract : The cover image, by Zhuolun Li et al., is based on the Research Article The paleoenvironmental significance of spatial distributions of grain size in groundwater‐recharged lakes: A case study in the hinterland of the Badain Jaran Desert, northwest China, DOI:10.1002/esp.4248 . Photo Credit: Zhuolun Li